A new phenotype of choreic syndrome associating severe freezing of gait and chorea. Issue 9 (2nd June 2020) - Laurens, Brice; Delleci, Claire; Goizet, Cyril; Spampinato, Umberto; Burbaud, Pierre; Guillaud, Etienne; Bestaven, Emma; Guehl, Dominique
Abstract: The early onset of gait akinesia should not rule out the diagnosis of hereditary chorea. It would be helpful to proceed to a whole‐genome and long‐read sequencing in order to track a new pathogenic variant including noncoding repeat expansion. Abstract : The early onset of gait akinesia should not rule out the diagnosis of hereditary chorea. It would be helpful to proceed to a whole‐genome and long‐read sequencing in order to track a new pathogenic variant including noncoding repeat expansion.